Fluid–solid coupled model for the internal erosion of gap‐graded soil–rock mixtures with different fines contents: Its verification and application. Issue 9 (2nd September 2022) - Cao, Zhilin; Sun, Weichen; Xie, Qiang; Wu, Zhihui; Fu, Xiang; Fumagalli, Alessio; Tian, Dalang; Liang, Li
Abstract: Soil–rock mixtures are widely encountered in geotechnical engineering projects. Gap‐graded soil–rock mixtures are prone to internal erosion because the fine particles are easily removed by seepage flow within the large pores between the coarse particles. Internal erosion has been the focus of geological disaster research. As concluded from different studies, the fines content (FC) of gap‐graded soils is a crucial factor in controlling soil stability. For this reason, a fluid–solid coupled model with the computational fluid dynamics—the discrete element method, with an indoor physical permeability test, was conducted to study the evolution characteristics of internal erosion of gap‐graded soil–rock mixtures of different FCs. After the erosion test, the vertical section of the sample was divided into three areas according to changes in fine particles: top, middle uniform, and bottom loss areas. The study showed that a large number of particles in the bottom loss areas are lost at first and the top loss area will enter the middle uniform loss areas. The fine particles in the middle are affected by the fine particle content, from accumulation to equilibrium to loss. Fine particle loss occurred at different sample heights. The top particle loss is the most serious, followed by the bottom and then the middle, and this is consistent with the changes, from a particle‐size perspective. An FC of 35% may be the critical value of the coarse‐fine particle skeleton structure in the preset working conditions of coarse and fine particle diameters. There are apparent 'island' effects in the sample where FC = 40%. This can be analysed through strong force chain analysis, from the particle‐size perspective that 'island' effects continue to disappear under the influence of internal erosion. Abstract : The spatial distribution of fine particle loss in the height direction could be divided into top, middle uniform, and bottom loss areas. (1) The absolute value of the pressure gradient change in the bottom and top of the sample is greater than that in the middle of the sample, and the more fine particles there are, the more obvious the change of pressure gradient. (2) From a meso‐mechanical (particle‐size) perspective, the contact number, coordination number, and strength force chain of particles are basically consistent with the particle migration. The structural stability in the middle loss areas is the best, followed by the bottom and then the top.